Modeling the amount of mineralized carbon from swine manure and wheat straw - de Paula, Gustavo Sérgio; Silva, Edilson Marcelino; Frühauf, Ariana Campos; da Silva, Édipo Menezes; Muniz, Joel Augusto; Fernandes, Tales Jesus (Revista Agrogeoambiental, 2020)
A method capable of reducing the environmental damage caused by swine manure and the soil enrichment with nutrients is based on the use of these residues together with the crops straw in soils for agricultural production. Through the use of carbon mineralization curves, it is possible to determine the best intervals for the use of organic matter from manure to better adapt the use of soil and crops. Dynamics of carbon present in manure can help in the selection of the best management. The objective of this study was to compare the fit of three nonlinear models that describe the carbon mineralization in soil over time, in addition to assessing the carbon stock of wheat straw alone and combined with swine manure. The experiment was carried out in a randomized block design, with four replications and eight treatments. The following treatments were tested: T1 – soil (S), T2 – soil + straw on the surface (SSUR), T3 – soil + incorporated straw (INCS), T4 – soil + manure on the surface (MSUR), T5 – soil + incorporated manure (INCM), T6 – soil + incorporated manure + straw on the surface (INCMSSUR), T7 - soil + incorporated manure + incorporated straw (INCMINCS), T8 – soil + straw on the surface + manure on the surface (SSURMSUR). Soil samples were incubated for 95 days, and ten observations were made throughout time. Carbon mineralization was described using nonlinear models Cabrera, Stanford and Smith and Juma, considering the autoregressive error structure AR (1), when necessary. The comparison of fit of models was made using the Akaike Information Criterion (AIC). The description of carbon mineralization of wheat straw and swine manure carried out by nonlinear models was satisfactory. The Cabrera model was the most appropriate to describe all treatments. The Stanford and Smith model, most used in the literature to describe the mineralization of organic waste in soil, did not achieve better results in relation to the other nonlinear models for the treatments under study. In general, the treatments with straw on the surface resulted in a larger carbon stock in the soil, and with the addition of manure to the wheat straw, the carbon stock was lower, so it is interesting for producers to evaluate, according to their production targets, which is the best strategy to be adopted for the use of waste.